Neurological, Cognitive, and Psychological Findings Among Survivors of Ebola Virus Disease From the 1995 Ebola Outbreak in Kikwit, Democratic Republic of Congo: A Cross-sectional Study. (10th August 2018) - Kelly, J Daniel; Hoff, Nicole A; Spencer, D'Andre; Musene, Kamy; Bramble, Matthew S; McIlwain, David; Okitundu, Daniel; Porco, Travis C; Rutherford, George W; Glymour, M Maria; Bjornson, Zach; Mukadi, Patrick; et al.
Abstract : Ebola survivors can have lower cognitive scores and more symptoms of depression and anxiety than close contacts more than 2 decades after an outbreak, suggesting these areas as potential long-term needs for >10000 West African Ebola survivors. Abstract: Background: Clinical sequelae of Ebola virus disease (EVD) have not been described more than 3 years postoutbreak. We examined survivors and close contacts from the 1995 Ebola outbreak in Kikwit, Democratic Republic of Congo (DRC), and determined prevalence of abnormal neurological, cognitive, and psychological findings and their association with EVD survivorship. Methods: From August to September 2017, we conducted a cross-sectional study in Kikwit, DRC. Over 2 decades after the EVD outbreak, we recruited EVD survivors and close contacts from the outbreak to undergo physical examination and culturally adapted versions of the Folstein mini-mental status exam (MMSE) and Goldberg anxiety and depression scale (GADS). We estimated the strength of relationships between EVD survivorship and health outcomes using linear regression models by comparing survivors versus close contacts, adjusting for age, sex, educational level, marital status, and healthcare worker status. Results: We enrolled 20 EVD survivors and 187 close contacts. Among the 20 EVD survivors, 4 (20%) reported at least 1 abnormal neurological symptom, and 3 (15%) had an abnormal neurological examination. Among the 187 close contacts, 14 (11%) reported at least 1 abnormal neurologic symptom, and 9 (5%) had an abnormal neurological examination. EVD survivors had lower mean MMSE and higher mean GADS scores as compared to close contacts (MMSE: adjusted coefficient: −1.85; 95% confidence interval [CI]: −3.63, −0.07; GADS: adjusted coefficient: 3.91; 95% CI: 1.76, 6.04). Conclusions: EVD survivors can have lower cognitive scores and more symptoms of depression and anxiety than close contacts more than 2 decades after Ebola virus outbreaks.